2019
DOI: 10.3390/foods8070260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sweet Corn Residue on Micronutrient Fortification in Baked Cakes

Abstract: Owing to the concept of modern life and health, traditional baked foods are seeking transition. In this study, sweet corn residue (SCR) was used to replace wheat flour in cakes. We conducted sensory evaluation and texture analysis to assess sample quality. Also, we simulated digestion in vitro, and determined the content of total sugar and dietary fiber. The content of vitamin E and carotenoids were determined by High Performance Liquid Chromatography (HPLC), and the content of folate was determined by a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Modern bakery trends include a variety of additives that increase commercial offerings, added value, and nutritional interests of their products. Lao et al [321] used sweet corn residue to replace wheat flour in cakes and found that the content of dietary fiber, folate, vitamin E, and carotenoids significantly increased, and digestive characteristics improved simultaneously. Furthermore, sweet corn residue cake had similar sensory qualities to the control, while slowing digestibility and providing more micronutrients.…”
Section: Bakingmentioning
confidence: 99%
“…Modern bakery trends include a variety of additives that increase commercial offerings, added value, and nutritional interests of their products. Lao et al [321] used sweet corn residue to replace wheat flour in cakes and found that the content of dietary fiber, folate, vitamin E, and carotenoids significantly increased, and digestive characteristics improved simultaneously. Furthermore, sweet corn residue cake had similar sensory qualities to the control, while slowing digestibility and providing more micronutrients.…”
Section: Bakingmentioning
confidence: 99%
“…Other than being utilized as a fresh or canned vegetable (Bender et al, 2013) -due to its rich source of antioxidants, vitamins, and minerals, it is also commonly used in production of processed foods and non-food products. For example, white corn beverages are gaining popularity as an alternative recovery drink for active people due to their high content of carbohydrate and protein levels (Jusoh et al, 2019); a modern bakery trend is the use of white corn residues to replace wheat flour in cakes due to its high nutrient content (dietary fiber, folate & Vitamin E) and increased digestive characteristics (Lao et al, 2019); there is an increasing trend in the use of corn sweeteners and high fructose corn syrup in the global sugar industries (Singh et al, 2014); bioenergy production using the white corn stalks and other residues (Pan-in and Sukasem, 2017); and use of white corn stalks as highly nutritious animal feeds/forage (Zhou et al, 2019) as an optimal management of agricultural waste practice. Notably, white corn is a food product consumed in diverse forms ranging from specialized foods in developed countries to staple cereal foods in developing countries (Malvar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%